2017
DOI: 10.1128/aem.00558-17
|View full text |Cite
|
Sign up to set email alerts
|

Polio and Measles Down the Drain: Environmental Enterovirus Surveillance in the Netherlands, 2005 to 2015

Abstract: Polioviruses (PVs) are members of the genus Enterovirus. In the Netherlands, the exclusion of PV circulation is based on clinical enterovirus (EV) surveillance (CEVS) of EV-positive cases and routine environmental EV surveillance (EEVS) conducted on sewage samples collected in the region of the Netherlands where vaccination coverage is low due to religious reasons. We compared the EEVS data to those of the CEVS to gain insight into the relevance of EEVS for poliovirus and nonpolio enterovirus surveillance. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 25 publications
3
40
0
Order By: Relevance
“…Nevertheless, EV-D68 was frequently detected in wastewater samples during reported outbreaks despite the fact that the virus is rarely found in stools from clinical cases (Barnadas et al 2017, Van Leer-Buter et al 2016). Although the presence of EV-D68 in sewage has been reported before (Benschop et al 2017, Brinkman et al 2017, Weil et al 2017), our finding was unexpected and suggests that EV-D68 might replicate in the gut more commonly than it is thought, perhaps during the initial stages of infection before respiratory symptoms develop and samples are collected for analysis. Although unlikely, the possibility that EV-D68 present in human respiratory fluids could reach the sewage system through washing, showering, etc.…”
Section: Resultssupporting
confidence: 45%
“…Nevertheless, EV-D68 was frequently detected in wastewater samples during reported outbreaks despite the fact that the virus is rarely found in stools from clinical cases (Barnadas et al 2017, Van Leer-Buter et al 2016). Although the presence of EV-D68 in sewage has been reported before (Benschop et al 2017, Brinkman et al 2017, Weil et al 2017), our finding was unexpected and suggests that EV-D68 might replicate in the gut more commonly than it is thought, perhaps during the initial stages of infection before respiratory symptoms develop and samples are collected for analysis. Although unlikely, the possibility that EV-D68 present in human respiratory fluids could reach the sewage system through washing, showering, etc.…”
Section: Resultssupporting
confidence: 45%
“…The most prevalent strains belonged to species B serotypes but EV strains from species A (CV-A4, CV-A6, and CV-A16), C (CV-A1, CV-A22, and EV-C109), and D (EV-D68) serotypes were also found. Previous studies have shown a high frequency of EV-B strains in Europe and the United States with the occasional expansion of EV-A and EV-D serotypes such as CV-A6, CV-A16, EV-A71, or EV-D68 ( Benschop et al, 2017 ; Brinkman et al, 2017 ). However, a high number of EV-C strains in sewage samples have been reported before in Scotland using direct PCR with EV species-specific primers ( Harvala et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…EV-D strains (all from serotype EV-D68) were only found in sewage samples from the United Kingdom. Studies using a variety of cell lines or direct molecular typing have shown the prevalence of EV-B strains in sewage in Europe and the United States (typically >75% of all EVs), with the occasional upsurge of EV-A and EV-D serotypes in recent years [ 15 , 21 ]. Interestingly, a recent study in Scotland identified a high quantity of EV-C strains in sewage samples (95 amplicons from 353 cloned EV sequences, 26.9%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%